2019
DOI: 10.1083/jcb.201909033
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and cancer: Modulation of cell death pathways and cancer cell adaptations

Abstract: Autophagy is intricately linked with many intracellular signaling pathways, particularly nutrient-sensing mechanisms and cell death signaling cascades. In cancer, the roles of autophagy are context dependent. Tumor cell–intrinsic effects of autophagy can be both tumor suppressive and tumor promotional. Autophagy can therefore not only activate and inhibit cell death, but also facilitate the switch between cell death mechanisms. Moreover, autophagy can play opposing roles in the tumor microenvironment via non–c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 156 publications
(198 reference statements)
0
97
0
Order By: Relevance
“…Considering the role of autophagy in cancer pathogenesis, we investigated whether CPT can modulate the autophagic signaling cascade. Autophagy is a degrading process in which autophagosomes package damaged organelles or cellular debris fused with lysosomes for degradation ( Levy et al, 2017 ; Towers et al, 2019 ). LC3, a widely used marker, plays a crucial role in autophagosome biogenesis and autophagy substrate selection ( Shi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the role of autophagy in cancer pathogenesis, we investigated whether CPT can modulate the autophagic signaling cascade. Autophagy is a degrading process in which autophagosomes package damaged organelles or cellular debris fused with lysosomes for degradation ( Levy et al, 2017 ; Towers et al, 2019 ). LC3, a widely used marker, plays a crucial role in autophagosome biogenesis and autophagy substrate selection ( Shi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then the transmission electron microscope observation combined with western blotting assay were used to confirm that DEH did cause endoplasmic reticulum stress in colorectal cancer cells in dose-and time-dependent manner. According to the previous reports, endoplasmic reticulum stress not only can increase autophagy but also can make autophagy inhibition [47,48].…”
Section: Discussionmentioning
confidence: 92%
“…In general, autophagy has been widely considered as a tumor suppressor mechanism at the stage of carcinogenesis, while tumor-promoting role of autophagy has been associated with progression of cancer, including melanoma [55,[64][65][66]. It has been demonstrated that autophagy suppressed melanomagenesis by promoting senescence, and decreased expression of ATG5 was sufficient to preclude this process [67].…”
Section: Autophagy In Melanomamentioning
confidence: 99%